Cognição espacial de muriquis-do-norte (Brachyteles hypoxanthus-Primates, Atelidae) - Marques, Karoline Luiza Sarges (2014)
Several species of primates live in large home ranges and travel extensive paths daily in search for food, water and sleeping sites. Studies indicate that primates travel in nonrandom manner, navigating between resources in a goal-oriented way, however, we are still far from understanding how these animals decode spatial information internally and how they use these information to navigate in their home ranges. We investigated the patterns of navigation of northern muriqui (Brachyteles hypoxanthus) in an Atlantic Forest fragment in the state of Espírito Santo, Brazil. We followed the muriquis for 87 days divided into two seasons of data collection: 2008/2009, when the scans samplings records were made every 10 minutes and in 2011/2012 when the scans records were made every 5 minutes. Our main goals were: 1) To investigate the orientation systems used by muriquis in their daily routes; 2) To investigate if there are changes in navigation speed and linearity depending on the resources exploited; 3) To investigate how muriquis choose their sleeping sites and how these areas are related to their daily range. Our results indicated that northern muriquis use a route-based map, connected by nodes, consistent with use of topological map. They travel faster when they are reaching food resources, resting and sleeping sites than when they are traveling to non-goal areas. The muriquis are selective in choosing their sleeping sites, choosing areas near to the nodes of the habitual route that provide thermal confort, protection and are close to foraging sites. Our data present evidences that muriquis travel in an efficiently and nonrandom way between resources in their habitat and that they have spatial knowledge about the resources in their home range.